2020
DOI: 10.3389/fvets.2020.00123
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation With Bacillus subtilis Direct-Fed Microbials Alters Chicken Intestinal Metabolite Levels

Abstract: Direct-fed microbials (DFMs) are dietary supplements containing live microorganisms which confer a performance and health benefit to the host, but the mechanisms are unclear. Here, a metabolomics approach was used to identify changes in intestinal metabolite levels in chickens fed an unsupplemented diet or a diet supplemented with B. subtilis strain 1781 or strain 747. Body weight gains of chickens fed the B. subtilis-supplemented diets were increased up to 5.6% in the B. subtilis 1781 group and 7.6% in the B.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 56 publications
1
30
1
Order By: Relevance
“…We observed that chickens given a diet containing Bacillus subtilis-based probiotics had a lower number of metabolic changes compared with the present report (31). More specifically, compared with unsupplemented controls, the levels of 83 metabolites were altered (25 increased, 58 decreased) in chickens given a diet supplemented with B. subtilis strain 1781, while 50 were altered (12 increased, 38 decreased) with a B. subtilis strain 747-supplemented diet.…”
Section: Discussioncontrasting
confidence: 65%
“…We observed that chickens given a diet containing Bacillus subtilis-based probiotics had a lower number of metabolic changes compared with the present report (31). More specifically, compared with unsupplemented controls, the levels of 83 metabolites were altered (25 increased, 58 decreased) in chickens given a diet supplemented with B. subtilis strain 1781, while 50 were altered (12 increased, 38 decreased) with a B. subtilis strain 747-supplemented diet.…”
Section: Discussioncontrasting
confidence: 65%
“…It has also been reported that several Bacillus strains, when used as DFM, have the ability to inhibit pathogens through the production of antimicrobials ( 38 , 39 ). Furthermore, Park et al ( 40 ) showed that broiler gut metabolites were altered by the Bacillus strain when used as DFM. They suggested that these metabolites might play a role in recognizing pathogen-associated molecular patterns (PAMPs) eventually leading to preventing intestinal disease and improving birds' growth.…”
Section: Resultsmentioning
confidence: 99%
“…For example, short-chain fatty acids, bacteriocins, functional peptides, and proteins are known as postbiotics (33,34); therefore, gut metabolites are considered as postbiotics. In our previous study (19), we performed a global metabolomic analysis of gut metabolites associated with growth and immunity enhancement following dietary exposure of young chickens with direct-fed microbes, B. subtilis 1781 and 747, which promote growth and immunity. Of the 361 metabolites that were altered in chickens treated with B. subtilis 1781 and 747, 131 metabolites were increased and 230 metabolites were decreased compared to the non-supplemented control group.…”
Section: Discussionmentioning
confidence: 99%
“…The animal study was reviewed and approved by the Beltsville Agricultural Research Center Small Animal Care Committee (Animal Protocol No. 19 The remaining authors declare that the research was conducted in the absence of any commercial or financial relationships that could be construed as a potential conflict of interest.…”
Section: Data Availability Statementmentioning
confidence: 99%
See 1 more Smart Citation